Hubungan Kematangan Emosi dengan Psikosomatis pada Mahasiswa Tingkat Akhir di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Putu Dita Hendrika Vijayanti; Sagung Putri Permana Lestari M.P; Komang Triyani Kartinawati (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Students in the final stage of lectures generally have academic and non-academic problems. Various problems that usually arise are when working on a final project (thesis) and having to complete lectures on time. This can develop into a negative feeling that can lead to a psychologically depressed state and ends up being uncomfortable. The power of problem solving objectively is based on the level of emotional maturity. The aim of the study was to find the correlation between emotional and psychosomatic maturity that occurred in the final stages of FKIK students at Warmadewa University. The sample used is the total number of affordable population, namely students from the class of 2017 who are taking semester VIII (92 people). The research method used is correlative analytic, cross sectional design. The data used are primary data obtained by interview using an emotional maturity scale questionnaire and a somatic symptom scale (SSS) questionnaire. Data analysis was carried out univariate also bivariate with Spearman correlation test. Spearman's correlation analysis showed a significant correlation between emotional and psychosomatic maturity that occurred in late-stage students at the Faculty of Medicine and Health Sciences at Warmadewa University (p=0.000), with a weak correlation (r= 0.415)